Pathways from Women's Group-based Programs to Nutrition Change in South Asia: A Conceptual Framework and Literature Review - Kumar, Neha (International Food Policy Research Institute, 2018)
This presentation was given during a webinar on May 9, 2018. Neha Kumar of the International Food Policy Research Institute (IFPRI) gave the presentation.